2023
DOI: 10.1002/aisy.202200239
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Electrohydraulic Soft Actuators

Abstract: Biodegradable materials decompose and return to nature. This functionality can be applied to derive robotic systems that are environmentally friendly. This study presents a fully biodegradable soft actuator, which is one of the key elements in “green” soft robotics. The working of the actuator is based on an electrohydraulic principle, which is similar to that of hydraulically amplified self‐healing electrostatic actuators. The actuator developed in this study consists of a dielectric film made of polylactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Notably, PLA has been used the most in the manufacture of BSSA. Numerous authors have reported that this material can be used as an SMP in thermal, [61,71,73,81,82,116,119,120,[123][124][125][126][127][128]132,133,196] electrothermal, [109] electrochemical, [135] magnetic, [69,75,78,82,197] and electrohydraulicbased [102,121] actuating soft systems. Several research groups have recently strengthened 3D-printed polymers by incorporating continuous fibers.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, PLA has been used the most in the manufacture of BSSA. Numerous authors have reported that this material can be used as an SMP in thermal, [61,71,73,81,82,116,119,120,[123][124][125][126][127][128]132,133,196] electrothermal, [109] electrochemical, [135] magnetic, [69,75,78,82,197] and electrohydraulicbased [102,121] actuating soft systems. Several research groups have recently strengthened 3D-printed polymers by incorporating continuous fibers.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…No-tably, from a material point of view, PLA has been employed the most in the fabrication of biodegradable soft actuators. Many authors have reported the applicability of this material as a SMP in thermal, [61,71,73,81,82,116,119,120,[123][124][125][126][127][128]132,133,197] electrothermal, [109] electrochemical, [135] magnetic, [69,75,78,82,197] and electrohydraulicbased [102,121] actuating soft systems.…”
Section: Fffmentioning
confidence: 99%
See 1 more Smart Citation